If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(7 + -6k) = -16 (7 * -9 + -6k * -9) = -16 (-63 + 54k) = -16 Solving -63 + 54k = -16 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '63' to each side of the equation. -63 + 63 + 54k = -16 + 63 Combine like terms: -63 + 63 = 0 0 + 54k = -16 + 63 54k = -16 + 63 Combine like terms: -16 + 63 = 47 54k = 47 Divide each side by '54'. k = 0.8703703704 Simplifying k = 0.8703703704
| -8+1=z-8 | | 5(x+7)=2(3x+2) | | 2y-12(y+1)-11y=15 | | 24z+3=5 | | 5x+5(4x+3)=165 | | 5/x-1+2/x+1=3/x-1 | | 6x+58=2x+26 | | 2x+3y=37 | | -6=1/5z-7 | | Ax+ab=2 | | Log(5x)-log(x+1)=4 | | 5t-7+5t=18 | | 2/3x8/1 | | 2x-3(-14-6x)=6 | | 2r-6y= | | d^2-d+1=0 | | 3a-4=5(3a-2) | | -9=1/2s-13 | | x+1/5-2=-4/x | | 3(2x-1)-11x=-3x+5 | | a+a+a+8+2=6+3+3a+a | | 7x+11=5x+15 | | 3x*2+6x=9 | | 9x+229=4x+129 | | 3e/5=3 | | (3x-6)/(2x-2) | | -2+32=x+14 | | 16=x/6-8 | | x^^2/3=16 | | 8b+4=3 | | ln(x)=4.1+ln(7.9) | | 5x-17=4c+36 |